Dilemas no cotidiano do orientador pedagógico: entre a confrontação com a profissão e a (auto) confrontação na formação docente - Mansano, Michel Serigato (2014)
The present work aimed to perform an analytical reading of collaborative activity that I develop as a Pedagogical Advisor, regarding the continuing education of teachers at the school where I work ( a city of São Paulo State). I used the narrative of memories to promote an observation process of some education paradigms that permeated the guidelines of my activity, and thus I could reflect about the position I have, emphasizing the teacher’s training focused on school (CANÁRIO) considering the historical and cultural assumptions of individuals involved in this experiment (VIGOSTSKI e BAKHTIN). In this work I assume the Pedagogical Advisor position essentially focused on the continuing education of teachers (PLACCO; ALMEIDA; SOUZA). The methodological procedure used was inspired by the analysis of professional practices on direct and cross self-confrontation (CLOT), which has been transformed by the individuals involved and it gave rise to a new process, different from the classic self-confrontations, that I termed only as confrontation. The analytical data reading, provided by the resulting dialogue (FREIRE e BAKHTIN) from the confrontations, indicated that the participating teachers in this study evidenced three movements: the perception of actions performed in the classroom, the speech organization to justify the pedagogical practices and teaching profession responsible acts (BAKHTIN). In this perspective, the confrontation proved to be an excellent tool to organize the Pedagogical Advisors work, as it allows gathering important information to plan, with teachers help, concrete initiation alternatives.